Intracellular Glucose-Depriving Polymer Micelles for Antiglycolytic Cancer Treatment - Lee, Jangwook; Kim, Kwangmeyung; Kwon, Ick Chan; Lee, Kuen Yong (WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim, 2023)
A new anticancer strategy to exploit abnormal metabolism of cancer cells rather than to merely control the drug release or rearrange the tumor microenvironment is reported. An antiglycolytic amphiphilic polymer, designed considering the unique metabolism of cancer cells (Warburg effect) and aimed at the regulation of glucose metabolism, is synthesized through chemical conjugation between glycol chitosan (GC) and phenylboronic acid (PBA). GC-PBA derivatives form stable micellar structures under physiological conditions and respond to changes in glucose concentration. Once the micelles accumulate at the tumor site, intracellular glucose capture occurs, and the resultant energy deprivation through the inhibition of aerobic glycolysis remarkably suppresses tumor growth without significant side effects in vivo. This strategy highlights the need to develop safe and effective cancer treatment without the use of conventional anticancer drugs.